Autonomy-withinrelationality: An alternative for architecture after the Global Financial Crisis - Reinmuth, Gerard; Benjamin, Andrew (Interstices: Journal of Architecture and Related Arts, 2020)
The 2008 Global Financial Crisis (GFC) triggered an upheaval within architecture reminiscent of the one accompanying the Great Depression. On both occasions, the discipline and profession reflected on their connection to each other, their boundaries and finally their relations to the insistent logic of capital. Specifically, the GFC led to a renewed focus on autonomy and its presence within architecture, was manifested in a number of different publications by Pier Vittorio Aureli, Nishat Awan-JeremyTill- Tatjana Schneider, Alejandro Zaera-Polo and Patrik Schumacher, however, all of these texts articulate the modalities of autonomy depending upon a restrictive definition of the architecture. In approaching the question of autonomy anew, we start with an assertion that the material and formal skills specific to architecture need to be understood as fundamentally relational in nature. In rethinking this manifestation, we propose an interconnection between autonomy and relationality identified and developed as autonomy within relationality.